THE EFFECT OF DIGITAL ABSENCE AND JOB SATISFACTION ON EMPLOYEE WORK PRODUCTIVITY AT PT PUTRATAMA SATYA BHAKTI BEKASI - Saputri, Anggraeni Dwi (BAIK Publishers, 2025)
This study aims to determine the effect of digital attendance and job satisfaction on employee productivity. The background of this research is based on the importance of utilizing technology in attendance systems and the role of job satisfaction in supporting employee performance. This study used a quantitative approach with a survey method. The number of respondents was 40 employees selected through purposive sampling. The data analysis technique used was multiple linear regression with SPSS. The results showed that, partially, digital attendance had a positive and significant effect on employee productivity, and that job satisfaction also had a significant effect on productivity. Simultaneously, digital attendance and job satisfaction also had a significant effect on employee productivity. The coefficient of determination of 0.657 indicates that 65.7% of the variation in employee productivity can be explained by these two variables, while the remainder is influenced by other factors outside this study. This finding reinforces the results of previous research and supports the theory that technology implementation and job satisfaction are important factors in increasing employee productivity